Non-invasive evaluation of blood flow through a healthy and stenosed coronary artery - Mohammed Ghalib Al-Azawy; Zahraa Ahmed Hamza; Alaa Ahmed Alkinani (Wasit Journal of Engineering Sciences)
The current numerical analysis was utilised to compare the hemodynamic effects caused by flow disruptions in coronary arteries with and without stenosis in order to evaluate the hemodynamic importance of patient-specific coronary stenosis using Computational Fluid Dynamics (CFD) to provide information to the public, particularly surgeons, and assist them in reducing the risk of stenosis. Assuming the flow is turbulent and non-Newtonian viscosity, the Carreau model is incorporated by utilizing STAR-CCM+ 2021.2.1. The test model is a patient-specific coronary stenosis with area stenosis (60%). The velocity, shear stress, and strain rate were evaluated and revealed that the stenosed artery experiences more hemodynamic impacts as the flow rate increases compared to the normal artery. The turbulent kinetic energy and turbulent viscosity ratio findings showed that the TKE and TVR are almost the same downstream of the stenoses, with the TKE and TVR being somewhat higher with the stenosed artery model than the unstenosed artery model, and it increases as the flow increases. Moreover, to determine the stenosis severity, the coefficient of pressure drop (CDP) and lesion flow coefficient (LFC) were used and showed that the CDP value be higher in stenosed artery (107pa) compared to a normal artery (5.2pa) but it was less when the flow increased (84.4pa), (2.5pa) respectively. whereas the LFC value in the stenoses artery is higher (0.61) and rises as flow increases (0.69).